2009
DOI: 10.1590/s1806-37132009001200006
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and practices related to smoking cessation among physicians in Nigeria

Abstract: Objective: To evaluate the knowledge and practices of smoking cessation among physicians in Nigeria. Methods: We conducted a cross-sectional survey in Lagos and three geopolitical zones of Nigeria. A self-administered structured questionnaire was used to obtain information on tobacco use and its health effects, as well as on the knowledge and practices of smoking cessation, from 436 physicians. Results: Of the 436 physicians, 292 (67.0%) were aware of smoking cessation, but only 132 (30.3%) showed good knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 11 publications
6
30
2
Order By: Relevance
“…Similar findings were observed in a study among physicians in Nigeria in which only 2.8% of the respondents prescribed nicotine replacement therapy to their patients. 24 These findings show that apart from occasionally screening for smoking and offering advice to quit, most healthcare providers did not go further to assist patients quit smoking.…”
Section: Discussionmentioning
confidence: 95%
“…Similar findings were observed in a study among physicians in Nigeria in which only 2.8% of the respondents prescribed nicotine replacement therapy to their patients. 24 These findings show that apart from occasionally screening for smoking and offering advice to quit, most healthcare providers did not go further to assist patients quit smoking.…”
Section: Discussionmentioning
confidence: 95%
“…It showed lower knowledge scores among the family physicians (54.3%) which were in nearly similar to results of a study by Desalu et al . [12] which found that 66.3% of the physicians had poor knowledge of smoking cessation interventions. This might be due to inadequate training in smoking cessation interventions after graduation and a lack of emphasis on smoking education in the medical curriculum, as the present study revealed that more than half of family physicians (57.3%) did not receive any training on smoking cessation skills either within under or postgraduate curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Even, in a study conducted among practicing physicians, only 30% had knowledge of smoking cessation therapy and 70% reported that tobacco education content in the medical school curriculum was inadequate. [9] This underscores the importance of training of professional health students in courses that detailed the harmful health effect of tobacco use and exposure to second smoke and specific training in counseling on tobacco cessation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smoking in general population is reported to be 8.9% in Nigeria,[6] however, the distribution of smoking is not the same across all the strata of the society. It varies from 7.7% among female secondary schools;[7] 17.1% among secondary school students;[8] 17.7% among physicians;[9] 20.3% among soldiers[10] to 37.9% among the general population in northern part of the country. [11]…”
Section: Introductionmentioning
confidence: 99%